Corporate social responsibility sophistication: Company-specific drivers among early and late adopters - Kyra Kunkel; Katharina Wigge; Rainer Lueg (Corporate Social Responsibility and Environmental Management, 2024)
Abstract This study examines the internal company drivers of corporate social responsibility (CSR) sophistication from a diffusion theory perspective. Bertram et al.'s (2015) framework on implementation drivers of innovations is used as our basis to operationalize the internal company drivers influencing CSR sophistication. We conduct fixed-effects regressions on a sample of 1919 international for-profit companies listed on the STOXX 1800 index (17,848 company years over the period 2002–2020) and explore several sub-portfolios. This study finds that management training, board skills, CEO compensation based on total shareholder return, and quality management systems drive CSR sophistication. Management training is the strongest and most consistent driver. Our analyses show that the effects of the identified drivers are strongest for portfolios of companies with previously low CSR sophistication. Moreover, early adopters appear to be motivated to utilize CSR for both economic reasons and legitimacy. While we find that board members with a finance background improve CSR sophistication, we also show that this increase mainly stems from improving governance practices. Last, we show that CSR sophistication notably increased over time, and parallel with the per capita wealth of the country that hosts its headquarters. Overall, this study is the first to investigate the internal company drivers of non-binary CSR sophistication using large-scale panel data, thereby exploring the effects of early/late adoption and the individual pillars of E, S, and G.
Keywords: 330; board skills; compensation; CSR sophistication; diffusion theory; early adoption; leadership skills; management training; quality management systems